Optimalisasi Literasi Anak Melalui Program Membaca Buku Nyaring (Read Aloud) Pada Peserta Didik TK dan SD di Desa Ekas Buana - Nila Kartika Hakim; Nur Hayani Ramdhani; Nila Sahara; Kelvin Harianto; Adim Rizman; Lalu Wahyu Andi Purnama (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Low reading interest and limited basic literacy skills among early childhood and primary school-aged children remain challenges in various regions, including Ekas Buana Village, East Lombok Regency. This situation is influenced by a lack of early reading habits and the increasing use of mobile phones for entertainment. One strategy to improve children's literacy is through "read-aloud" activities, which create interactive, enjoyable learning experiences suited to children's developmental characteristics. This initiative aimed to boost reading interest and basic literacy skills among kindergarten (TK) and primary school (SD) students (grades 1–3) in Ekas Buana Village. A participatory read-aloud method was employed, implemented by 15 university students participating in the Community Service Program (KKN). The program comprised initial observation, coordination with schools, regular read-aloud sessions, Q&A sessions, discussions, educational games, reflection, and teacher training to ensure program sustainability. The results indicate that students participated enthusiastically and actively in discussions, were able to retell the stories, and showed improvements in vocabulary, listening skills, and reading comprehension. Furthermore, teacher training provided an understanding of the read-aloud method, creating the potential for the literacy program to continue in the long term. Thus, read-aloud activities have proven to be an effective strategy for fostering a literacy culture and enhancing basic literacy skills among children in Ekas Buana Village.